2021
DOI: 10.51894/001c.18182
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bedside Ultrasound for Gallstone Disease Care within a Community-based Emergency Department: A Confirmation Bias

Abstract: INTRODUCTION Traditional evaluation for suspicion of gallstone or gallbladder-related disease includes evaluation with a formal technician-performed ultrasound. However, the use of point-of-care bedside ultrasounds (Bedside US) has been shown to be a viable alternative for the diagnosis of gallstones and gallbladder-related diseases. Purpose Statement : The purpose of this study was to evaluate the impact of Bedside US use in gallbladder evaluation on key patient care ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…55 Resource utilisation in the ED Fourteen articles described the effect of POCUS on resource utilisation in the ED when used on patients with symptoms suspicious of biliary disease (Table 5). [13][14][15][16][57][58][59][60][61][62][63][64][65][66] In all 14 articles, POCUS operators were ED doctors, with variable levels of POCUS expertise, where specified. Seven were retrospective observational studies, [13][14][15]61,62,64 and five were prospective observational studies.…”
Section: Pocus Operator Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Resource utilisation in the ED Fourteen articles described the effect of POCUS on resource utilisation in the ED when used on patients with symptoms suspicious of biliary disease (Table 5). [13][14][15][16][57][58][59][60][61][62][63][64][65][66] In all 14 articles, POCUS operators were ED doctors, with variable levels of POCUS expertise, where specified. Seven were retrospective observational studies, [13][14][15]61,62,64 and five were prospective observational studies.…”
Section: Pocus Operator Trainingmentioning
confidence: 99%
“…[13][14][15][16][57][58][59][60][61][62][63][64][65][66] In all 14 articles, POCUS operators were ED doctors, with variable levels of POCUS expertise, where specified. Seven were retrospective observational studies, [13][14][15]61,62,64 and five were prospective observational studies. 16,57,58,60,63 There was one case series 59 and one case report.…”
Section: Pocus Operator Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Patients who have biliary disease diagnosed by POCUS, and are managed without confirmatory imaging, have on average a 2-hour shorter length of stay in the ED. [9][10][11] Despite the literature demonstrating reliability and potential benefits of biliary POCUS, there has been a lack of adoption for the purpose of surgical decision-making. 12 A recent Canadian national survey showed that 60% of practicing surgeons had a total lack of confidence in ED POCUS for the diagnosis of biliary disease.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of POCUS can improve access to care, and more emergency medicine physicians are being trained in biliary POCUS 8. Patients who have biliary disease diagnosed by POCUS, and are managed without confirmatory imaging, have on average a 2-hour shorter length of stay in the ED 9–11. Despite the literature demonstrating reliability and potential benefits of biliary POCUS, there has been a lack of adoption for the purpose of surgical decision-making 12.…”
Section: Introductionmentioning
confidence: 99%